2020
DOI: 10.3390/toxins12060363
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soil Bacterium Strain Desulfitobacterium sp. PGC-3-9 Detoxifies Trichothecene Mycotoxins in Wheat via De-Epoxidation under Aerobic and Anaerobic Conditions

Abstract: Trichothecenes are the most common mycotoxins contaminating small grain cereals worldwide. The C12,13 epoxide group in the trichothecenes was identified as a toxic group posing harm to humans, farm animals, and plants. Aerobic biological de-epoxidation is considered the ideal method of controlling these types of mycotoxins. In this study, we isolated a novel trichothecene mycotoxin-de-epoxidating bacterium, Desulfitobacterium sp. PGC-3-9, from a consortium obtained from the soil of a wheat field known for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The 3- epi -DON, intermediate 3-keto-DON, and deepoxy-DON (DOM-1) all displayed reduced toxicity relative to DON [ 24 , 39 ]. Microbes responsible for de-epoxidation have been isolated from animal gut microflora and soil environments [ 4 , 44 , 45 , 48 ]. For example, under anaerobic conditions, bacterial consortia such as Eubacterium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3- epi -DON, intermediate 3-keto-DON, and deepoxy-DON (DOM-1) all displayed reduced toxicity relative to DON [ 24 , 39 ]. Microbes responsible for de-epoxidation have been isolated from animal gut microflora and soil environments [ 4 , 44 , 45 , 48 ]. For example, under anaerobic conditions, bacterial consortia such as Eubacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the present study explained why and how the key structural elements and substituents of trichothecenes impact their toxic actions through the binding interactions with the eukaryotic ribosome. Interestingly, these key toxicity-contributing structural elements have been targeted to develop detoxification strategies towards trichothecenes [43], such as the reductive de-epoxidation at C 12,13 epoxide ring [44][45][46], and the epimerization at C 3 -OH [10,11,47]. The epimerization and de-epoxidation are two microbial biotransformation pathways reported for DON detoxification with 3-epi-DON and deepoxy-DON (DOM-1) as the metabolized products.…”
Section: Implications Of the Mechanism Behind Structure-activity Relamentioning
confidence: 99%
“…A novel bacterial strain able to de-epoxify DON was recently isolated from a wheat field soil and identified as Desulfitobacterium sp. PGC-3-9 [ 125 ]. After a 24 h incubation under anaerobic or aerobic conditions at 37 °C in the minimum medium containing yeast extract, pyruvate, and fumarate (MMYPE medium) supplemented with 500 μg/mL DON, the level of a DON degradation reached 99 and 95%, respectively.…”
Section: Biotransformation Of Deoxynivalenolmentioning
confidence: 99%
“…Massive screening techniques using diverse methods have been conducted to identify DON-degrading microbes, several of which have high DON conversion ability. Over the last three decades, DON-degrading strains have been identified among genera including Eubacterium (Fuchs et al, 2002), Eggerthella (Gao et al, 2018), Desulfitobacterium (He et al, 2020), Devosia (He et al, 2016;Wang et al, 2017Wang et al, , 2019, Sphingomonas (Ito et al, 2013;He et al, 2017), Nocardioides (Ikunaga et al, 2011), Marmoricola (Ito et al, 2012, Bacillus (Li et al, 2011), Pelagibacterium (Zhang et al, 2020), and Aspergillus (He et al, 2008;Jaqueline and Eliana, 2010;Jaqueline et al, 2011;Yang et al, 2017).…”
Section: Biodegradation Of Deoxynivalenol Bymentioning
confidence: 99%
“…In the past, it was thought that the conversion of DON to DOM-1 could only be completed under anaerobic conditions; however, recent studies have shown that Desulfitobacterium sp. PGC-3-9 can transform DON under both anaerobic and aerobic conditions ( He et al, 2020 ). The genus Devosia has been widely studied, and several species in this genus can detoxify DON.…”
Section: Introductionmentioning
confidence: 99%